The black book [large type] - Patterson, James, 1947-; Ellis, David, 1967- (Little, Brown and Company, 2017)
Being a cop runs in Billy Harney's family. The son of Chicago's Chief of Detectives whose twin sister, Patty, also followed in their father's footsteps, there's nothing Billy won't give up for the job, including his life. Left for dead alongside his former partner and a district attorney, Billy miraculously survives. But he remembers nothing about the events leading up to the shootout. The investigation leads to an unexpected address -- an exclusive brothel that caters to Chicago's most powerful citizens. There's plenty of incriminating evidence on the scene, but what matters most is what's missing: the madam's black book. Now shock waves are rippling through the city's elite, and everyone's desperate to find it. Billy suspects the black book contains the truth that will either set him free ... or confirm his worst fears.